Clara Louisa Penney, List of books printed before 1601 in the Library of the Hispanle Society of America. Offset reissue, with additions. The Hispanic Society of America, New York, 1955; xiv + 305 pp., 1 facs. (Hispanic notes & monographs, Catalogue series). - Serís, Homero (El Colegio de México, 1956)
Se reseñó el libro: List of books printed before 1601 in the Library of the Híspanle Society of America. Offset reissue, with additions.